Digital Marketing Strategy for Local Agribusiness Products in Indonesia - Tri Waluyo (Jurnal Sosial Sains dan Komunikasi, 2022)
With the growth of technology and increasingly widespread internet penetration in Indonesia, digital marketing has become crucial for increasing the visibility and competitiveness of local agribusiness products. This research aims to identify and analyze effective digital marketing strategies to support the growth and market penetration of local agribusiness products in Indonesia. This research uses a qualitative approach with descriptive methods. The research results show that implementing digital marketing strategies for local agribusiness products in Indonesia has had a positive impact in increasing product visibility, expanding market reach, and increasing consumer engagement. Through the use of social media, optimizing online content, QR codes on product packaging, and participation in e-commerce platforms, local agribusiness producers are able to create closer relationships with consumers and increase product competitiveness in the digital market. Organizing online training sessions or webinars has also proven effective in empowering local farmers to adopt digital marketing strategies effectively. Overall, this research shows that the integration of digital technology in the marketing of local agribusiness products is an important step to increase the growth of this sector in the era of digital and globalization.